Numerical analysis and optimization of remotely pumped double pass Erbium doped fiber amplifier - Hossain, Nadir; Naji, Ahmed W.; Mishra, Vivekanand; Mohammed, Abbou F.; Rashid, Hairul A. A.; Rahman, Faidz Abd. (IEICE-INST ELECTRONICS INFORMATION COMMUNICATIONS ENG, 2007)
A simple rate equation model of double pass (DP) Erbium doped fiber amplifier (EDFA) is developed based on the Giles and Desurvire ( 1991) model of single pass (SP) EDFA. The mathematical equations to calculate stimulated absorption and emission rate between level 1 and 2 of SP EDFA are modified by integrating the reflected backward propagating signal of DP EDFA. Reflection loss of signal by the reflector is included with the backward propagating signal of DP EDFA. A combination of Runge-Kutta and relaxation method is used to numerically solve the developed DP EDFA rate equation model. Considering high gain and low noise figure (NF) by very low remote pump power as main design objective, the design procedure of remotely pumped optimized DP EDFA is described. Finally the robustness and stability of the developed DP EDFA rate equation model are shown by analyzing the numerical results and output shape using various design parameters.